2020
DOI: 10.1088/1674-1056/ab610a
|View full text |Cite
|
Sign up to set email alerts
|

Shape reconstructions and morphing kinematics of an eagle during perching manoeuvres*

Abstract: The key to high manoeuvre ability in bird flight lies in the combined morphing of wings and tail. The perching of a wild Haliaeetus Albicilla without running or wing flapping is recorded and investigated using a high-speed digital video. A shape reconstruction method is proposed to describe wing contours and tail contours during perching. The avian airfoil geometries of the Aquila Chrysaetos are extracted from noncontact surface measurements using a ROMBER 3D laser scanner. The wing planform, chord distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…These maneuvers help sustain pitch stability. In order to counter adverse yaw characteristics, the bird performs twisting maneuvers with its tail that enables it to maintain yaw stability [16]. Another maneuver that the bird performs as a stimulus to decrease in lift generation is wing tucking.…”
Section: Control Surface Dynamicsmentioning
confidence: 99%
“…These maneuvers help sustain pitch stability. In order to counter adverse yaw characteristics, the bird performs twisting maneuvers with its tail that enables it to maintain yaw stability [16]. Another maneuver that the bird performs as a stimulus to decrease in lift generation is wing tucking.…”
Section: Control Surface Dynamicsmentioning
confidence: 99%
“…[5] Three-dimensional (3D) laser scanners were used to reconstruct the shape of bird wings to analyze kinematics during flight. [6] Because birds use their wings in different ways in different flight movements, their roles in adjusting the position during complicated maneuvering remain largely unknown. At present, there are three main ways to study the flight posture of birds (as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] They can actively change speed and direction, complete cruising, soaring, turning, landing, diving, and other incredible motions. [4][5][6][7] Shatkovska [8] found that birds with different wing morphology have different flight patterns. Liu et al [9] conducted a 3D scanning of the wing geometry of several birds and established a flapping avian wing model with correct kinematics.…”
Section: Introductionmentioning
confidence: 99%